Fly ash for sustainable construction - Nayak, Dheeresh Kumar (Elsevier Ltd, 2022)
Concrete has a tremendous influence on the environment since the majority of its composition is cement, which is a material that emits high levels of carbon dioxide. It is possible for concrete construction to have a lower impact on the environment if the usage of cement is reduced as much as possible by the addition of mineral admixtures such as fly ash, without sacrificing the durability standards at the same time. The disposal of fly ash, which is produced by power stations that burn coal for fuel, is recognised as one of the most pressing environmental issues. When there is a simultaneous increase in the amount of fly ash and a decline in the capacity of landfills, it is much more difficult to find a solution to this problem. The research on fly ash admixed concrete is analysed and discussed in this publication. There have been many studies conducted on the topic of fly ash concrete and its beneficial effects. In this study, the fresh and hardened properties of fly ash concrete, such as mechanical properties, durability parameters, and microstructural characteristics, are studied. Additionally, the useful application case studies of fly ash concrete published by the American Coal Ash Association are also summarised. © 2022 The Author(s)
A review of fly ash concrete and its beneficial use case studies
Keywords: Carbonation; Durability properties; Filler effect; Fly ash (FA)